Development Of Interactive Learning Media Based On Lumio By Smart On Basic Elements Of Accounting And Institutional Finance At SMKN 1 Surabaya - M. Iqbal Fauzi Al Hasany; Suci Rohayati (Journal of Innovative and Creativity, 2025)
The digital era has driven a significant transformation in the world of education, one of which is through the development of digital learning media that is effective in increasing learner motivation and understanding. This study aims to examine the process of developing interactive media based on Lumio by SMART on Basic Elements of Accounting and Institutional Finance at SMK Negeri 1 Surabaya, test the feasibility of the product, and analyse students' responses to its use in learning. This media development uses the 4-D model, but is only carried out up to the Develop stage. The results showed that the feasibility of content reached 83.75%, presentation 87.5%, language 94.28%, and graphic 98%, with an overall average of 94% which is classified as very feasible. Learners' responses also showed a very high level of understanding, with an average percentage of 97%. Based on expert validation and learner responses, Lumio by SMART-based learning media on Basic Elements of Institutional Accounting and Finance is declared very feasible to use in the learning process.